Clausewitz on Auctions - Samuel Häfner (University of Basel, Center of Business and Economics (WWZ), 2012)
A multi-stage model on the course of war is presented: Individual battles are modeled as private value all-pay auctions with asymmetric combatants of two opposing teams. These auctions are placed within a multi-stage framework with a tug-of-war structure. Such framing provides a microfounded rationale for the use of the popular logit Tullock contest success function in models of militarized conflicts, yields new theoretical justification for existing empirical findings with respect to war, and provides new hypotheses regarding strategic battlefield behavior.
Keywords: D74; F51; H56; 330; Auction; War; Multi-Stage Contest; Tug-of War; Tullock Contest Success Function; Microfoundation; Krieg; Rationalität; Auktionstheorie; Theorie